2015
DOI: 10.1111/vop.12272
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the prevalence of corneal surface disease in dogs receiving prophylactic topical lubrication under general anesthesia

Abstract: 14Objective: To identify the prevalence of corneal ulceration in dogs receiving prophylactic 15 gel lubrication under general anesthesia (GA). 16Materials and Methods: An ophthalmic examination was performed before 17 premedication and 24h after GA in 100 dogs (199 eyes) undergoing non-ophthalmic 18 procedures. Individuals with known pre-existing ocular surface conditions were excluded. Conclusions:The results of this study show that a basic protocol 33 of prophylactic lubrication during GA was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 18 publications
1
38
2
Order By: Relevance
“…The case counts used in previous publications on CUD have generally been small [5, 7–10, 16–29]. Although the overall study population of some of these earlier studies may have included up to 200 animals [5, 21, 26], the count of CUD cases within each population, when clearly presented, often dropped to much lower numbers [5]. Furthermore, many of these earlier studies only included referral caseloads, which introduces inevitable selection bias into the study design [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case counts used in previous publications on CUD have generally been small [5, 7–10, 16–29]. Although the overall study population of some of these earlier studies may have included up to 200 animals [5, 21, 26], the count of CUD cases within each population, when clearly presented, often dropped to much lower numbers [5]. Furthermore, many of these earlier studies only included referral caseloads, which introduces inevitable selection bias into the study design [11].…”
Section: Discussionmentioning
confidence: 99%
“…Primary causes of CUD in dogs include spontaneous chronic corneal ulceration (SCCED) [5, 10, 16] and canine herpes virus-1 [17]. Multiple secondary causes are reported, including entropion [18, 19], ectopic cilia [8, 20], primary and secondary forms of keratoconjunctivitis sicca (KCS) [7, 21], corneal degeneration [22], traumatic events [23–25], corneal overexposure related to general anesthesia [26], facial nerve paralysis [27] and orbital diseases [28, 29]. Many of these factors have also been associated with certain breed phenotypes [30] and some smaller studies based on referral populations of less than 250 cases have reported increased CUD prevalence in breed-types such as brachycephalic [7, 31, 32] or spaniel types [7, 33].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent prospective study [14] in dogs receiving prophylactic eye instillation of a carmellose sodium gel at induction and every 2-4 h during GA, a low incidence (0.5%) of superficial corneal ulcerations, but a high incidence of corneal epithelial erosions (18.6%) were reported.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that the reduction of reflex tear formation during anaesthesia may be due to the depression of autonomical pathways responsible for the production of tears. This decrease is usually transient but may last for several days when combined with other postoperative complications (Martin 2005b, Dawson and Sanchez 2016). …”
Section: Discussionmentioning
confidence: 99%